The Effectiveness of Desferrioxamine Administration by Retained IV Catheter into Subcutaneous towards Pain and Satisfaction in Thalassemic Patients - Kaennak, Ruenrudee; Srijakkot, Jitpinan; Jetsrisuparp, Arunee; Chathum, Kannika (Srinagarind Medical Journal, 2020)
Background and objective: Desferrioxamine injection is a method of treatment for iron overloaded thalassemic patients, recommended by subcutaneous injection. Currently using retained Butterfly needle into subcutaneous, causing pain and dissatisfaction, therefore it was changed to retained IV Catheter into subcutaneous.The purpose of this research was to evaluate the effectiveness of Desferrioxamine administration by Retained IV Catheter into Subcutaneous towards pain and Satisfaction in Thalassemic Patients. Methods : This investigation was a Quasi-experimental research, one group pretest – posttest design.Selected by purposive sampling focused on 30 inclusion criteria patients.The research tool were 1) A pain assessment 2) A satisfaction assessment.Data was analyzed by using frequency, percentage,means,standard deviation,and Paired t-test. Results : The results showed that using Desferrioxamine injection by retained IV-Catheter into subcutaneous, patients had overall pain at the level of no pain (0.40±0.81). While retained butterfly needle into subcutaneous, the patients had moderate pain (5.40±1.19). Comparison the pain of both injection methods, it was found that there were statistically significant differences (p<0.001). Whereas the satisfaction of Desferrioxamine injection by retained IV-Catheter into subcutaneous is the highest level (4.40±0.50), while the butterfly needle was at a moderate level (2.87±0.35) and found that satisfaction with both methods has statistically significant differences (p<0.001). Conclusion : An iron chelotor, Desferrioxamine injection by retained IV-Catheter into subcutaneous, thalassemic patients had less pain and more satisfaction than retained butterfly needle into subcutaneous.